A physiological and histological atlas of reproduction in the North American deer mouse (Peromyscus maniculatus) - Kathryn Wilsterman; Megan J. Hemmerlein; Anna Isabel Bautista; Natalie M. Báez-Torres; Kaylinn M. Gosney; Kylie E. Jewett; Ashley M. Larson; Ellery L. Myers (PLoS ONE, 2025)
The North American deer mouse (Peromyscus maniculatus) exhibits extensive diversity in morphology, physiology, and life history across its broad range. These traits have propelled the deer mouse to model system status across several fields within the biological sciences. Nonetheless, we still lack basic knowledge about some important aspects of this species’ biology. For example, limited information about the deer mouse’s reproductive physiology remains a significant barrier to developing genetic tools for the species and for advancing our current understanding of how this species has been so evolutionarily successful. Here, we aim to fill this knowledge gap by (1) characterizing body temperature profiles across reproductive stages and (2) generating a detailed histological atlas of placental development. We show that body temperature can be used to diagnose copulation and pregnancy in deer mice, however body temperature cannot be used to predict fertility (likelihood to breed) prior to pairing individuals. Our histological atlas of placental development represents the first day-by-day developmental timeline of the placenta in a Peromyscus species; using this atlas, we describe unique organization and behaviors of trophoblast cells in the deer mouse. Together, these descriptive datasets provide substantial new comparative data on reproductive physiology in Cricetids, and they provide a foundation for further functional work in this important model species.